Endoscopic management of refractory gastroesophageal reflux disease. (3rd April 2018) - Seleem, Waseem M.; Hanafy, Amr Shaaban; Mohamed, Samir I.
Abstract: Objective: Despite the therapeutic and surgical interventions for the management of gastroesophageal reflux disease (GERD), yet the high cost and the post-operative complications had led to a significant socioeconomic burden. The aim was to evaluate the safety and efficacy of endoscopic band ligation (EBL) in the management of refractory GERD. Methods: A total of 150 patients with refractory GERD were assigned to an EBL group (banding was done at four quadrants just at the gastroesophageal junction (GEJ) ( n  = 75) or to a control group (optimized dose of PPI, n  = 75). Follow-up for both groups by upper GI endoscopy to evaluate the site of the Z line from the incisors, the width of the GEJ and the coaptation of GEJ around the endoscope on retroflection. PH monitoring was performed every 3 months with GERD- QoL assessment monthly for 1 year. Results: In EBL group; 58 patients (77.3%) needed 1 session, 17 patients (22.7%) needed 2 sessions. 4 rubber bands were utilized in 44 patients (58.7%), 3 rubber bands in 31 patients (41.3%). Follow-up for 1 year revealed a highly significant improvement of the GERD- QoL score, the site of Z line with significant reduction of reflux episodes and symptom index when compared to the medical treatment group. In EBL group; there were no major adverse events including bleeding, post band ulcers, stenosis at one year follow up. Conclusion: The current study provides a novel endoscopic intervention to treat refractory GERD, which is safe, cost-effective, with no major adverse effects at one year follow up.